2020
DOI: 10.1016/j.redox.2019.101398
|View full text |Cite
|
Sign up to set email alerts
|

On the epigenetic role of guanosine oxidation

Abstract: Chemical modifications of DNA and RNA regulate genome functions or trigger mutagenesis resulting in aging or cancer. Oxidations of macromolecules, including DNA, are common reactions in biological systems and often part of regulatory circuits rather than accidental events.DNA alterations are particularly relevant since the unique role of nuclear and mitochondrial genome is coding enduring and inheritable information. Therefore, an alteration in DNA may represent a relevant problem given its transmission to dau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 215 publications
(261 reference statements)
2
48
1
Order By: Relevance
“…This is indeed in keeping with pull-down and Western blot assays showing that the G4 motifs of the KRAS promoter form together with PARP-1, MAZ and hnRNP A1 the transcription pre-initiation complex. It is possible that 8OG behaves as an epigenetic mark for the recruitment to the promoter of the transcription factors [ 51 , 52 , 53 ]. We observed that PARP-1 binds to both G4 32R and G4 mid, either in a wild-type or oxidized form.…”
Section: Resultsmentioning
confidence: 99%
“…This is indeed in keeping with pull-down and Western blot assays showing that the G4 motifs of the KRAS promoter form together with PARP-1, MAZ and hnRNP A1 the transcription pre-initiation complex. It is possible that 8OG behaves as an epigenetic mark for the recruitment to the promoter of the transcription factors [ 51 , 52 , 53 ]. We observed that PARP-1 binds to both G4 32R and G4 mid, either in a wild-type or oxidized form.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of guanosine to 8-oxo-7,8-dihydroguanosine (8-oxo-dG) is the most frequent oxidation product in DNA. 46 Compared to adenosine, guanosine might therefore likewise be more prone to bleaching processes. Biomarker ratios of decreasing guanosine and increasing adenosine were formed, but did not result in improved discrimination.…”
Section: Marker Interpretationmentioning
confidence: 99%
“…It was also found that the levels of o 8 dGuo noticeably increased with the increase of the Air Quality Index, and the method is a viable tool to investigate the relationship between o 8 dGuo levels and the effect of air pollution. o 8 dGuo removal is tightly regulated by external and internal stimuli, e.g., ROS accumulation that is affected by air pollution as well ( Figure 12) [7].…”
Section: Resonance Light Scattering Aptasensor Based On Magnetic Nanomentioning
confidence: 99%
“…OG may alter gene expression and its transcriptional impact is dependent on the coding versus template strand of OG occurrence, and it can temporarily stop or even completely abolish mRNA synthesis. The role of guanine lesions is the complex process of epigenetic regulation that has been reviewed recently by several authors [1,5,[7][8][9][10][11][12][13][14][15][16][17]. Pertinent to this multifaceted role is the analytical detection, quantification and structural studies of the facilitated formation of OG in G-rich oligonucleotide sequences, in particular, G-quadruplexes and their hydrolysis products (nucleosides, nucleobases), which is the subject of the present review.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation